Assessing the Influence of Land-Use Changes on Water Quality Using Remote Sensing and GIS: A Study in Cirata Reservoir, Indonesia - Sunardi Sunardi; Ilya Nursamsi; Moh. Dede; Amalia Paramitha; Mochamad Chandra Wirawan Arief; Miranti Ariyani; Prihadi Santoso (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Environmental Changes in a round of reservoir have dramatic influences on the sedimentation and deterioration of water quality. A significant land-use change in Cibalagung sub-watershed has impact on the water quality in the Cirata reservoir. In this study, we used remote sensing and GIS to investigate the influence of land-use changes on water quality in Cibalagung sub-watershed, Cirata reservoir in 2004–2014. The influence of land-use changes on total suspended solids (TSS), as a main parameter of water quality, was determined by path analysis. This study indicated that 92.50 % of land-use changes through increasing mixed plantations, cropland, settlements, and grassland could affect the TSS content in the reservoir.